Anti-GAD65 Antibodies Related Refractory Epilepsy Successfully Treated with Tocilizumab: A Case Report and Systematic Literature Review - Chen S; Kessi M; Tan J; He F; Zhang C; Yin F; Yang L; Peng J (ImmunoTargets and Therapy)
Shimeng Chen,1 Miriam Kessi,1 Jielu Tan,1– 3 Fang He,1– 3 Ciliu Zhang,1– 3 Fei Yin,1– 3 Lifen Yang,1– 3 Jing Peng1– 3 1Department of Pediatrics, Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 2Hunan Intellectual and Developmental Disabilities Research Center, Pediatrics, Changsha, People’s Republic of China; 3Clinical Research Center for Children Neurodevelopmental Disabilities of Hunan Province, Xiangya Hospital, Central South University, Changsha, People’s Republic of ChinaCorrespondence: Lifen Yang, Department of Pediatrics, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China, Tel +86-1367435745, Fax +86-731-84327332, Email yanglifen7@126.comBackground: Although anti-GAD65 related epilepsy is rare, it needs more attention because it is refractory to the conventional therapies, has poor outcome and high relapse rate. In this study, we intended to report the efficacy of tocilizumab in the treatment of anti-GAD65 antibodies related refractory epilepsy based on our center’s experience and literature review.Methods: The clinical data of the patients managed with tocilizumab at Xiangya Hospital and those from the literature was collected and analysed.Results: A female child presented at our center with neuropsychiatric symptoms and generalized tonic-clonic seizures (including status epilepticus) at the age of 3 years. She had positive anti-GAD65 autoantibodies. Her initial electroencephalograph showed multi-focal epileptic discharges and an early brain magnetic resonance imaging demonstrated increased intensity in the bilateral hippocampi and right insular cortex. She received several anti-seizures medications (ASMs) and immunotherapies without significant improvement; however, she experienced significant clinical, electrographic and radiological improvement after receiving four cycles of the tocilizumab. Literature review unveiled two more female cases. The mean age of seizure onset for three cases was 7.72 years, and they presented with refractory seizures (n=3), neuropsychiatric symptoms (n=3), ataxia (n=2), and anti-GAD autoantibodies were elevated in both the serum and cerebrospinal fluid (n=3). All three cases tried several combinations of ASMs and immunotherapies before tocilizumab but they remained with refractory epilepsy. Following several cycles of the tocilizumab, all cases had significant positive changes: seizure freedom (n=1), seizure control (n=2), improved-normal cognition (n=3), improved neuropsychiatry symptoms (n=2) and controlled ataxia (n=2).Conclusion: Tocilizumab seems to be an effective therapy for the refractory anti-GAD65 related epilepsy as it can control seizures, improve cognition and neuropsychiatric symptoms.Keywords: anti-GAD65 autoantibodies, epilepsy, tocilizumab, efficacy, safety, review